Diabetic mice have retinal and choroidal blood flow deficits and electroretinogram deficits with impaired responses to hypercapnia. - Eric R Muir; Divya Narayanan; Saurav B Chandra; Nikolay P Akimov; Jeong-Hyeon Sohn; Evan Meyer; René C Rentería; Timothy Q Duong (PLoS ONE)
Purpose The purpose of this study was to investigate neuronal and vascular functional deficits in the retina and their association in a diabetic mouse model. We measured electroretinography (ERG) responses and choroidal and retinal blood flow (ChBF, RBF) with magnetic resonance imaging (MRI) in healthy and diabetic mice under basal conditions and under hypercapnic challenge. Methods Ins2Akita diabetic (Diab, n = 8) and age-matched, wild-type C57BL/6J mice (Ctrl, n = 8) were studied under room air and moderate hypercapnia (5% CO2). Dark-adapted ERG a-wave, b-wave, and oscillatory potentials (OPs) were measured for a series of flashes. Regional ChBF and RBF under air and hypercapnia were measured using MRI in the same mice. Results Under room air, Diab mice had compromised ERG b-wave and OPs (e.g., b-wave amplitude was 422.2±10.7 μV in Diab vs. 600.1±13.9 μV in Ctrl, p < 0.001). Under hypercapnia, OPs and b-wave amplitudes were significantly reduced in Diab (OPs by 30.3±3.0% in Diab vs. -3.0±3.6% in Ctrl, b-wave by 17.9±1.4% in Diab vs. 1.3±0.5% in Ctrl). Both ChBF and RBF had significant differences in regional blood flow, with Diab mice having substantially lower blood flow in the nasal region (ChBF was 5.4±1.0 ml/g/min in Diab vs. 8.6±1.0 ml/g/min in Ctrl, RBF was 0.91±0.10 ml/g/min in Diab vs. 1.52±0.24 ml/g/min in Ctrl). Under hypercapnia, ChBF increased in both Ctrl and Diab without significant group difference (31±7% in Diab vs. 17±7% in Ctrl, p > 0.05), but an increase in RBF was not detected for either group. Conclusions Inner retinal neuronal function and both retinal and choroidal blood flow were impaired in Diab mice. Hypercapnia further compromised inner retinal neuronal function in diabetes, while the blood flow response was not affected, suggesting that the diabetic retina has difficulty adapting to metabolic challenges due to factors other than impaired blood flow regulation.